The Usefulness of Capacity Cost Reports in Increasing Profit Performance: An Experimental Study - Jesica Handoko (The Indonesian Journal of Accounting Research, 2013)
One of the recent innovations in modern managerial accounting is the practice of reporting unused capacity costs. This experimental study is conducted using a 2x2x2x2x12 mixed-subjects design aiming to answer: (1) whether reporting unused capacity cost is benefiting to decision maker, that will reduce unused capacity; (2) whether, by considering market demand fluctuation in long-term periods, decision makers who receive capacity cost reports will outperform the other decision makers who did not receive capacity cost reports; (3) whether a linear model could be used to reduce negative impact (decreasing profit) that is suggested to be caused by capacity cost reports; and (4) whether locus of control interacts with capacity cost report to influence companies’ profit performance.One hundred and fifty eight undergraduate students of FEUKWMS participated in this experiment after they were deemed to have passed the manipulation checks and answered the research questions in full. There are several findings: first, by considering the within-subject period, this experiment supports a previous study (Buchheit, 2003), which found significant influence from interaction of variable Period*Cap_Rep*Demand to capacity decision (F-value 2.5806, p-value <0.05); second, 12 periods of within-subject couldn’t prove the anchoring-and-adjustment bias which causes non-optimally capacity cost reports benefit; third, there is an emerging indication about the influence of linear model and/or locus of control on a company’s performance, although it isn’t statistically significant. This provides evidence that implementing modern management accounting innovations needs objective mathematical/statistical tools and/or subjective consideration that arise from decision makers’ locus of control.